2018
DOI: 10.1093/gigascience/giy014
|View full text |Cite|
|
Sign up to set email alerts
|

Bipartite graphs in systems biology and medicine: a survey of methods and applications

Abstract: The latest advances in high-throughput techniques during the past decade allowed the systems biology field to expand significantly. Today, the focus of biologists has shifted from the study of individual biological components to the study of complex biological systems and their dynamics at a larger scale. Through the discovery of novel bioentity relationships, researchers reveal new information about biological functions and processes. Graphs are widely used to represent bioentities such as proteins, genes, sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 264 publications
(271 reference statements)
0
107
0
2
Order By: Relevance
“…While this approach is extremely challenging in wild snakes, whose movements and interactions are difficult to track, bipartite networks can be used to examine connections between two sets of data, such as species and disease traits, and illuminate overall trends. These networks are defined by having two sets of nodes and no two nodes within the same set adjacent 30 . A bipartite network analysis conducted to look for associations with chytridiomycosis in frogs observed that skin sloughing rate varied with phylogenetic group, but there was no evidence that sloughing was associated with Bd-driven population declines 31 .…”
Section: Discussionmentioning
confidence: 99%
“…While this approach is extremely challenging in wild snakes, whose movements and interactions are difficult to track, bipartite networks can be used to examine connections between two sets of data, such as species and disease traits, and illuminate overall trends. These networks are defined by having two sets of nodes and no two nodes within the same set adjacent 30 . A bipartite network analysis conducted to look for associations with chytridiomycosis in frogs observed that skin sloughing rate varied with phylogenetic group, but there was no evidence that sloughing was associated with Bd-driven population declines 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Species belonging to the "higher" group correspond always to columns, and species belonging to "lower" group always correspond to rows of the matrix. Using this convention, competencies are equivalent to species belonging to the "higher" group, and values of the set correspond to species from the "lower" group (Pavlopoulos et al, 2018).…”
Section: Bipartite Model For Competency Analysismentioning
confidence: 99%
“…proteins, genes, small molecules, metabolites, ligands, diseases, drugs) in order to unravel how complex systems operate. Despite the great variety of visualization tools to efficiently represent such networks [1][2][3][4][5][6] , visualization still remains a bottleneck as views often become incomprehensive due to the large number of nodes and edges. Therefore, ways to visually focus on the important parts of a network emerge.…”
Section: Introductionmentioning
confidence: 99%